2022
DOI: 10.15212/ijafr-2022-0014
|View full text |Cite
|
Sign up to set email alerts
|

Solutions to enteric methane abatement in Ireland

Abstract: The efficiency of Ireland’s grass-based livestock systems can be attributed to high outputs, low production costs and a low carbon footprint relative to housed systems. Methane (CH4) is a potent greenhouse gas (GHG) of which enteric fermentation from livestock production is a key source, being directly responsible for 57% of Irish agricultural GHG emissions. There are a number of strategies including dietary manipulation and breeding initiatives that have shown promising results as potential mitigation solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…Scenario 2 (S2), on the other hand, involves a larger scaling of immediate technologies as well as the adoption of innovations such as the use of additives, representing a model that would be more likely to be adopted by a risk-tolerant farmer. The Bovaer (3NOP) additive has been trialled at FZC for methane reduction, and based on these results and the results of previous studies, a 28% reduction was estimated during housing with a 10% reduction throughout the grazing period [40][41][42]. The environmental impact is limited to GHG emissions (carbon footprint) only.…”
Section: Modelling Different Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…Scenario 2 (S2), on the other hand, involves a larger scaling of immediate technologies as well as the adoption of innovations such as the use of additives, representing a model that would be more likely to be adopted by a risk-tolerant farmer. The Bovaer (3NOP) additive has been trialled at FZC for methane reduction, and based on these results and the results of previous studies, a 28% reduction was estimated during housing with a 10% reduction throughout the grazing period [40][41][42]. The environmental impact is limited to GHG emissions (carbon footprint) only.…”
Section: Modelling Different Scenariosmentioning
confidence: 99%
“…The adoption rate of additives in general is expected to be low, as there are issues regarding social acceptance and the cost of the additives [65]. Previous studies have suggested the use of slow-release bolus to incorporate the additives in pasture-based systems where 95% of the animals' diet is from grazed forage [41,63].…”
Section: Environmental Impactmentioning
confidence: 99%
“…That said, signs of starvation, evidenced via observations of 'poor' body condition, were present across many of the carcasses. Tern starvation may be due to factors such as climate change and extreme weather events impacting parental care and provisioning rates (Baird 1990;Dias et al 2019;Piec & Dunn 2021), pollution (Dias et al 2019), fluctuating food availability/food shortages (Monaghan 1992;Suddaby & Ratcliffe 1997;Piec & Dunn 2021), provision of poor quality food items (Harris et al 2008;Schrimpf et al 2012), and competition with commercial fisheries (Camphuysen & Garthe 2000), particularly those targeting important seabird prey items such as sandeels (Mitchell et al 2020;Cook et al 2014) and sprat (Cummins et al 2016). Indeed, Roseate Terns have low behavioural plasticity regarding prey items (Monaghan 1992) and may therefore be particularly susceptible to the effects of prey shortages.…”
Section: Morphology and Body Conditionmentioning
confidence: 99%